Refleksi dan Self-Assessment dalam Pembelajaran PAI Berbasis Kurikulum Merdeka : Upaya Meningkatkan Kesadaran Spritual dan Karakter Religius Peserta Didik - Muhammad Rusman Hadi; Lubna; Mukhlis (Mataram University, 2026)
This study aims to analyze the role of reflection and self-assessment in Islamic Religious Education (PAI) learning based on the Kurikulum Merdeka in enhancing students’ spiritual awareness and religious character. This research employs a qualitative library research approach by examining relevant books, scientific journals, and contemporary educational studies. The findings indicate that the integration of reflective activities such as reflective journals, group discussions, and spiritual portfolio encourages students to internalize Islamic values beyond cognitive understanding. Furthermore, the implementation of self-assessment through religious attitude sheets, worship evaluation scales, and value-based rubrics strengthens students’ self-regulated learning and moral responsibility. Reflection and self-assessment contribute significantly to the development of self-awareness, improved quality of worship, honesty, and consistent spiritual behavior. These strategies transform assessment from a judgment-oriented process into a growth-oriented and reflective practice aligned with the dimension of faith and noble character within the curriculum framework. Therefore, reflection and self-assessment function not merely as evaluation tools but as transformative pedagogical approaches to foster authentic spiritual consciousness and sustainable religious character formation among students.